Sustainability materiality of insuring coal businesses for insurers - Umakanth, Mithula (Frontiers in Sustainability, 2024)
Insurance is a tool that transfers risks which businesses face. A recent study shows that losses arising from natural calamities is rising at an increased rate and insurers must be cautious in managing their exposures (Hinshaw Law, 2021). Therefore, financial institutions are increasingly investing and insuring those companies that are environment friendly to better align client needs and broader society objectives (Gunnar Friede, 2015).This study aims to understand the impact of sustainability efforts on materiality or financial performance of insurers taking in to account their risk coverage pattern in the Coal Mining Industry. Major insurance companies operating in the US Insurance industry are considered for this study.